1995
DOI: 10.1093/tropej/41.5.285
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Growth Hormone (GH), Insulin-like Growth Factor-I (IGF-I) and Free Thyroxine, GH Response to Clonidine Provocation and CT Scanning of the Hypothalamic-pituitary Area in Children with Sickle Cell Disease

Abstract: Serum growth hormone (GH), cortisol, free thyroxine (FT4), thyroid-stimulating hormone (TSH), and insulin like growth factor I (IGF-I) concentrations were measured in 15 children with sickle cell disease (SCD) together with their heights < 5th percentile for age and gender, and in 15 healthy age-matched children who had normal variant short stature (NVSS). GH response to an oral dose of clonidine (0.15 mg/m2) and cortisol response to ACTH stimulation were determined in the two groups. Children with SCD had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
11
0
1
Order By: Relevance
“…88 Interest in growth hormone dysfunction has motivated a series of studies by Soliman and co-workers who demonstrated abnormalities in the growth hormone (GH)/insulinlike growth factor-I (IGF-I) axis. 54,[89][90][91][92] In a study of 21 pre-pubertal SS children with poor growth (height ,10th centile), defective GH secretion and low insulin-like IGF-1 and IGF binding-protein-3 were demonstrated in 43%, with a reduced response of IGF-1 production to GH injection. The disease severity score was significantly higher in the group with defective GH secretion than in the group with normal GH secretion.…”
Section: Endocrine Dysfunction and Growth Retardationmentioning
confidence: 99%
“…88 Interest in growth hormone dysfunction has motivated a series of studies by Soliman and co-workers who demonstrated abnormalities in the growth hormone (GH)/insulinlike growth factor-I (IGF-I) axis. 54,[89][90][91][92] In a study of 21 pre-pubertal SS children with poor growth (height ,10th centile), defective GH secretion and low insulin-like IGF-1 and IGF binding-protein-3 were demonstrated in 43%, with a reduced response of IGF-1 production to GH injection. The disease severity score was significantly higher in the group with defective GH secretion than in the group with normal GH secretion.…”
Section: Endocrine Dysfunction and Growth Retardationmentioning
confidence: 99%
“…The authors concluded that vascular insult to the hypothalamicpituitary axis appears to be the cause of growth failure in these patients 6 . b measured serum GH and IGF-I, using Clonidine provocation, in 15 patients with SCD with short stature (heights -2 SD or more below the mean) and compared them to healthy age-matched children with normal variant short stature.…”
Section: Discussionmentioning
confidence: 97%
“…Brought to you by | University of California -San Francisco Authenticated Download Date | 2/20/15 2:50 PM deficiency was associated with growth failure in one study, and pituitary infarction has also been proposed as a cause of GH deficiency in patients with sickle cell disease with short stature 6 .…”
mentioning
confidence: 99%
“…In support of this effect, testicular and pituitary gland volumes of patients with SCD are reported to be smaller with many infarcts in the testicles and pituitary gland. [222340]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the transfusion-dependent type of SCD, iron toxicity may also add to different organ damage including the pituitary gland and gonads. [212223]…”
Section: Introductionmentioning
confidence: 99%